MODEL REKRUTMEN BERBASIS KOMPETENSI PADA BISNIS RITEL DI KOTA MEDAN - Rukmini, Rukmini; Harahap, Nurain; Safina, Wan Dian (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The study aims to produce an abstraction model for employee recruitment. The competency based recruitment Model is expected to be practically applied to the recruitment of manpower, as an effort to reduce the unemployment rate in Medan. This research was conducted on the business sector of retail. Retail business is a business category that absorbs labor, despite its small business scale, the turnover is also small but can contribute to improve the development of the country's economy through the tax sector, this retail business is a business sector that is widely found in Indonesia.  Technical analysis of data in the study using qualitative descriptive methods and conducting data collection through interviews to be able to obtain information about the recruitment model of competency based employees. It then used a quantitative descriptive method with Karl Pearson's Correlation Product Moment method to achieve recruitment outcomes on employee performance. The results showed that the recruitment applied by the company was open and online based on the company's website and the determination of levels and qualifications in accordance with the competencies set by the company.